Inhibitory Role of the Mud Crab Short Neuropeptide F in Vitellogenesis and Oocyte Maturation via Autocrine/Paracrine Signaling - Bao, Chenchang; Yang, Yanan; Huang, Huiyang; Ye, Haihui (Frontiers in Endocrinology, 2018)
Neuropeptides, in addition to their classical role in the nervous system, act on intraovarian factors to regulate reproductive functions in vertebrates. However, this function of neuropeptides has not been characterized in crustaceans. Short neuropeptide F (sNPF), a highly conserved invertebrate neuropeptide, has been reported to be involved in feeding, metabolism, and in differentiation processes including reproduction. Although sNPF and its receptor (sNPFR) have been detected in the ovary in different species, ovarian colocalization of sNPF/sNPFR has not been investigated. In this study, we identified Scylla paramamosain (mud crab) sNPF (Sp-sNPF) as an endogenous ligand for the S. paramamosain orphan G protein-coupled receptor NPY2R in mammalian cell line HEK293T. We designated this receptor as Sp-sNPFR. RNA in situ hybridization in pre-vitellogenic ovary and reverse transcription-PCR on isolated denuded oocytes and follicle layers showed that Sp-sNPF was exclusively localized to the follicle cells, whereas Sp-sNPFR was detected in both follicle cells and oocytes. We also found that Sp-sNPF partly suppressed spontaneous maturation of denuded oocytes and caused intracellular cAMP accumulation and Ca2+ mobilization. Moreover, injection of synthetic Sp-sNPF peptides inhibited the expression of vitellogenin and vitellogenin receptor genes in vivo. These combined results suggest for the first time that Sp-sNPF may have inhibitory functions in vitellogenesis and oocyte maturation possibly via the autocrine/paracrine pathway.